The effectiveness and safety of ofatumumab for the treatment of pemphigus vulgaris: a cohort study based on a registry database - Zhang, Xiwen; Wang, Yiyi; Tan, Ping; Zhou, Xingli; Xiao, Yue; Feng, Xun; Li, Jishu; Wei, Mintong; Zou, Min; Kim, Gyeongah; Jiang, Lu; Li, Xiaohong; et al. (Frontiers in Immunology, 2025)
BackgroundOfatumumab, a fully human anti-CD20 monoclonal antibody administered subcutaneously and indicated for multiple sclerosis, might theoretically be effective for patients with pemphigus vulgaris (PV).ObjectiveTo evaluate the effectiveness and safety of ofatumumab in patients with PV.MethodsThis cohort study was based on a registry database of autoimmune bullous diseases at West China Hospital (AIBD-WCH), including two groups. One was ofatumumab (OFA) group, involving patients receiving ofatumumab subcutaneous injections (2×20mg, 2 weeks apart) and systemic glucocorticoids with/without immunosuppressant. The glucocorticoids control (GC) group was matched using propensity score matching in a 1:2 ratio based on sex, age and body mass index. Both groups completed regular follow-up for 52 weeks. The primary endpoint was the proportion of patients achieving complete remission during therapy (CRDT) at week 52. Secondary endpoints included maintaining treatment (MT) with daily prednisone doses <0.2 mg/kg/d, relapse rate, the change of pemphigus disease area index and cumulative glucocorticoid doses. Safety results were also collected.ResultsSixteen and thirty-two patients were included in OFA and GC groups, respectively. At week 52, more patients in OFA group achieved CRDT (31.2% versus 3.12%, p=0.012) and MT (68.8% versus 25.0%, p=0.009). Furthermore, patients in OFA group took lower cumulative glucocorticoid doses by week 52 (6186 [SD: 1177]mg versus 9317 [SD: 1579]mg, p<0.001). A patient in OFA group experienced gastric hemorrhage, which was judged to be unrelated to ofatumumab, while two in GC group developed lung infections.ConclusionsOfatumumab combined with glucocorticoids demonstrated favorable effectiveness compared with GC group, without increasing severe adverse events.